The Effect of the Use of Gadgets on the Learning Outcomes of Social Studies Subjects in Class V of SD Inpres Bumi Sagu - Widiani, Ni Nyoman; Gagaramusu, Yusdin Bin. M.; Lapasere, Sisriawan; Azizah, Azizah (FKIP - Universitas Riau, 2025)
This study aims to find out the existence and absence of the Influence of Gadget Use on Student Learning Outcomes in Class V of SD Inpres Bumi Sagu. The population in this study is all grade V students of SD Inpres Bumi Sagu for the 2024/2025 school year totaling 30 students, 15 VA class students as experimental classes and 15 VB class students as control classes. Sampling was done using purposive sampling techniques. Data collection using a multiple-choice test totaling 15 questions. Data analysis used Normality Test, Homogeneity Test, and Hypothesis Test. The test was carried out with the help of the IBM SPSS Statistics program version 27. The results of hypothesis testing using the Paired Sample T-Test or paired samples with the help of the IBM SPSS version 27 program showed that the significance values (<0.001) < (0.05) which means Ha were accepted so that there was an influence of the use of gadgets on student learning outcomes in grade V of SD Inpres Bumi Sagu.